Dehydration of Pentanediol over CeO2, CeO2‐Ga2O3, and CeO2‐In2O3. Issue 14 (19th May 2017) - Gnanamani, Muthu Kumaran; Jacobs, Gary; Shafer, Wilson D.; Hopps, Shelley D.; Davis, Burtron H.
Abstract: Conversion of bio‐oil from flash pyrolysis of biomass is a way to produce useful renewable feedstocks for the chemicals industry. Dehydration of pentanediol (1, 5‐ and 2, 4‐pentanediol) was investigated over CeO2, CeO2 ‐Ga2 O3, and CeO2 ‐In2 O3 catalysts at 250–350 °C. Adding Ga or In (20 mol%) improved the conversion of pentanediol over CeO2, but adversely affected selectivity. In the base case, 1, 5‐pentanediol was converted on CeO2 to 4‐penten‐1‐ol and 1‐pentanol, desired linear alcohols, together with unwanted cyclopentanol and cyclopentanone byproducts. Adding gallium or indium to ceria increased the selectivity towards undesired cyclized products like tetrahydropyran and tetrahydropyran‐2‐one due to increased acidity. In the base case, 2, 4‐pentanediol converted on CeO2 to unsaturated alcohol (e. g., 3‐penten‐2‐ol > 74 % selectivity), but adding Ga or In promoted acid‐catalyzed cracking. Tuning the acid‐base characteristics of ceria significantly alters the product distribution. Abstract : The addition of gallium or indium enhanced the partial reduction of ceria. The oxygen deficient sites on ceria as well as acidity are responsible for the observed activity and selectivity of gallium or indium modified ceria for dehydration of 1, 5‐petanediol and 2, 4‐pentanediols. CeO2 ‐Ga2 O3 and CeO2 ‐In2 O3 both promote the cyclized products formation than linear monoalcohols from 1, 5‐pentanediol. On the other hand, 2, 4‐pentanediol involved in cracking over both CeO2 ‐Ga2 O3 and CeO2 ‐In2 O3 catalysts.